2021
DOI: 10.3390/ani11113234
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Genomic and Pedigree Inbreeding Coefficients in Small Cattle Populations

Abstract: This study aimed to identify inbreeding coefficient (F) estimators useful for improvement programs in a small Holstein population through the evaluation of different methodologies in the Mexican Holstein population. F was estimated as follows: (a) from pedigree information (Fped); (b) through runs of homozygosity (Froh); (c) from the number of observed and expected homozygotic SNP in the individuals (Fgeno); (d) through the genomic relationship matrix (Fmg). The study included information from 4277 animals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…The inbreeding coefficient is a fundamental tool for livestock husbandry: It is necessary for increasing the accuracy of the genomic and genetic breeding value of animals and the consequent improving of the breeds [ 29 ]; it is one of the main parameters to monitor the selection programs; it is also useful in biodiversity conservation, allowing to identify possible pitfalls in terms of loss of genetic variability; and it helps breeders to choose the best mating schemes to improve animal welfare and to avoid inbreeding depression (which is especially relevant when using the AI) [ 30 ]. As previously mentioned, genomic inbreeding coefficients are more reliable than pedigree-based ones, being free from possible registration inaccuracy [ 4 , 11 ]. This is the reason why the implementation of genomic tools at the field level has increased, leading to genomic selection programs not only in cattle but also in other farm animals such as sheep and goats [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inbreeding coefficient is a fundamental tool for livestock husbandry: It is necessary for increasing the accuracy of the genomic and genetic breeding value of animals and the consequent improving of the breeds [ 29 ]; it is one of the main parameters to monitor the selection programs; it is also useful in biodiversity conservation, allowing to identify possible pitfalls in terms of loss of genetic variability; and it helps breeders to choose the best mating schemes to improve animal welfare and to avoid inbreeding depression (which is especially relevant when using the AI) [ 30 ]. As previously mentioned, genomic inbreeding coefficients are more reliable than pedigree-based ones, being free from possible registration inaccuracy [ 4 , 11 ]. This is the reason why the implementation of genomic tools at the field level has increased, leading to genomic selection programs not only in cattle but also in other farm animals such as sheep and goats [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genomic information allows for a more accurate inbreeding estimation by overcoming pedigree inconsistencies and by accounting for the Mendelian sampling. This allows to better decipher the genetic variation between the individuals, which is of great interest primarily in small and endangered populations, and to eventually estimate unbiased genetic values [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the association analysis the phenotypes were the predicted transmitting abilities (PTA) of milk, fat, protein yield and conformation final score; information provided by the National Center for Disciplinary Research in Physiology and Animal Improvement of the National Institute for Forestry, Agriculture and Livestock Research (INIFAP) [ 22 ]. The association analyses were performed with a linear regression of the PTA on the ROH [ 2 , 11 ] with the SNP & Variation Suite v8.3 [ 19 ] and the ARS-UCD1.2 [ 23 ] database was used as a reference for searching annotations related with the regions found in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, several studies have shown methodologies to calculate the inbreeding coefficient of an individual through the ROH, quantifying the proportion of the genome covered by ROH [9][10][11]. These methods can be used to calculate how recent or old the inbreeding is in the population and give a real proportion of the genome that is homozygous [12].…”
Section: Introductionmentioning
confidence: 99%
“…Embora bastante eficiente, proporcionando grandes avanços no controle da endogamia em rebanhos sob seleção, algumas limitações puderam ser observadas em relação ao referido método. O fato de o cálculo do coeficiente de endogamia depender diretamente das informações de pedigree suscetibilizou a ocorrência de erros na estimação, uma vez que em lacunas referentes a genealogia dos indivíduos são bastante comuns, em especial em rebanhos pequenos, inviabilizando o cálculo de indivíduos não conectados à estrutura do pedigree (CORTES-HERNÁNDEZ et al, 2021).…”
Section: Coeficiente De Endogamia Via Pedigreeunclassified